2017
DOI: 10.1021/acs.biochem.7b00781
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Functional Evaluation of the Intramolecular Disulfide Bonds in the Zinc-Chelating Antimicrobial Protein Human S100A7 (Psoriasin)

Abstract: Human S100A7 (psoriasin) is a metal-chelating protein expressed by epithelial cells. It is a 22-kDa homodimer with two EF-hand domains per subunit, and two transition-metal-binding His3Asp sites at the dimer interface. Each subunit contains two cysteine residues that can exist as free thiols (S100A7red) or as an intramolecular disulfide bond (S100A7ox). Herein, we examine the disulfide bond redox behavior, the Zn(II) binding properties, and the antibacterial activity of S100A7, as well as the effect of Ca(II) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 60 publications
7
32
0
Order By: Relevance
“…1012,1417,20 Nevertheless, investigations of CP-Ser 20 as well as the host-defense proteins S100A7 34 and S100A12 35 have demonstrated that His 3 Asp sites sequester Zn(II). Moreover, studies of metal depletion from microbial growth media indicate that His 3 Asp sites select for Zn(II) over other metals, including Ni(II).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1012,1417,20 Nevertheless, investigations of CP-Ser 20 as well as the host-defense proteins S100A7 34 and S100A12 35 have demonstrated that His 3 Asp sites sequester Zn(II). Moreover, studies of metal depletion from microbial growth media indicate that His 3 Asp sites select for Zn(II) over other metals, including Ni(II).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, studies of metal depletion from microbial growth media indicate that His 3 Asp sites select for Zn(II) over other metals, including Ni(II). 14,34,35 We therefore sought to examine metal exchange at the His 3 Asp site using the pull-down assay described above. Efforts to purify a biotinylated His 4 variant resulted in poor yields because the protein routinely precipitated, and we were unable to readily obtain sufficient quantities of this protein for the assay.…”
Section: Resultsmentioning
confidence: 99%
“…Disulfide bond reduction may be assisted by extracellular glutathione, a tripeptide with antioxidant functions that is localized both intracellularly and extracellularly [44]. As a second option, we deem it to be possible that a fraction of the P2 × 4R head domain disulfide bonds may be in a redox balance between free SH and its oxidized form as demonstrated for psoriasin (S100A7), which is released from epithelial cells in two forms, one oxidized and another reduced [45]. We are aware that Zn(II) cannot reduce disulfides (as it does for instance metallic zinc [46]) but our data strongly supports that somehow the alkylation process depends on Zn(II).…”
Section: Discussionmentioning
confidence: 99%
“…S100 proteins occur mainly as homodimers (Barger et al, 1992; Giannakopoulos et al, 1996; Matsui Lee et al, 2000; Cunden et al, 2017). Specifically, it is known that calcium binding to S100 proteins triggers conformational changes that expose a hydrophobic cleft that is crucial to interaction with partners to their activation, regulation and signaling functions.…”
Section: The S100 Protein Familymentioning
confidence: 99%